The Response of River‐Resident Fish to Reservoir Freshet Releases of Varying Profiles Intended to Facilitate a Spawning Migration. Issue 6 (1st June 2020) - Baker, N. J.; Taylor, M. J.; Cowx, I. G.; Harvey, J. P.; Nunn, A. D.; Angelopoulos, N. V.; Smith, M. A.; Noble, R. A.; Tinsdeall, M.; Baxter, J.; Bolland, J. D.
Abstract: Natural hydrological regimes encompass varying seasonal flow characteristics that provide fish with cues and opportunities for upstream spawning migrations, but these flows are often modified/absent in regulated rivers. Compensatory artificial flows (freshets) can be released from reservoirs to replicate these characteristics, but studies testing their effectiveness are limited. To address this, river‐resident brown trout, a species known to undertake spawning migrations, were manually tracked using radio telemetry in a regulated upland river in northern England in response to 11 freshet releases of differing timing, magnitude, and duration. Spawning migrations were not observed because extent of movement during freshets was generally small and the pattern of movement (i.e., directionality and relocation indices) was comparable between impact/control reaches. Movements during freshets were comparable with those observed the days immediately before/after and were small relative to the entire tracking period. In conclusion, freshet characteristic of those recommended to produce "naturalized" autumn/winter flow elevations did not stimulate/facilitate spawning migrations of river‐resident brown trout under the given seasonal conditions. Outside freshets, longer unidirectional movements occurred during low‐flow periods and elevated river level due to rainfall, including during periods of reservoir overtopping. Notwithstanding, fish in experimental reaches were significantly more active (total distance moved) and occupied a larger extent of river (range during freshet) than those in control reaches during short‐duration freshets. Therefore, during dry years/when (autumn/winter) reservoir overtopping events are unlikely, small‐magnitude freshets providing flows that allow fish short opportunities to search for/find superior local habitat while minimizing total water released are recommended. Key Points: Artificial freshets from reservoirs are promoted in international guidance to stimulate spawning migrations of fish River‐resident brown trout did not perform spawning migrations during freshets of differing timing, magnitude, and duration These findings are important for water resource managers when designing ecologically appropriate flow regimes for regulated rivers